Outcomes in three cases after brivaracetam treatment during pregnancy. (24th January 2020) - Paolini, Stephanie L.; Pilato, Madison; Rajasekaran, Vijayalakshmi; Waters, Janet F. R.; Bagic, Anto; Urban, Alexandra
Abstract : Background: Use of certain antiseizure drugs (ASDs) during pregnancy increases the risk of major congenital malformations, while less is known about newer ASDs. Based on the safety of levetiracetam, brivaracetam may be similarly safe in pregnancy; however, no cases have been published to date. Aims of the Study: We retrospectively identified three women with epilepsy treated with brivaracetam during pregnancy and described the maternal and neonatal outcomes. Methods: We reviewed the patients' medical records as well as the linked medical records of their infants to identify complications during pregnancy and delivery, neonatal complications, and evidence of major/minor congenital malformations. Results: Our series included one woman with idiopathic generalized epilepsy and two women with focal epilepsy (brivaracetam doses ranging from 50 to 200 mg daily). One patient with focal epilepsy experienced breakthrough seizures, and lamotrigine was added to brivaracetam. The other women had no neurologic complications during pregnancy. All three women had full‐term deliveries without significant complications. Three healthy infants were born with Apgar scores of 9 and 9 and no major congenital malformations. Three minor congenital malformations were observed in two infants. Conclusions: While the absence of major congenital malformations in these cases is encouraging, further data are needed to determine the safety of brivaracetam in pregnancy.